2021
DOI: 10.1002/nop2.1129
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nurse‐led counselling and education on self‐efficacy of patients with acute coronary syndrome: A randomized controlled trial

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…In this study, demographic characteristics revealed an average age of 55.66 years in the control group and 54.69 years in the intervention group, closely aligning with prior research indicating mean ages of 57.03 and 59.28 years for intervention and control groups, respectively (15). The majority of participants were married, mirroring findings from previous studies that reported high marriage rates among patients with coronary artery disease (16,17).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, demographic characteristics revealed an average age of 55.66 years in the control group and 54.69 years in the intervention group, closely aligning with prior research indicating mean ages of 57.03 and 59.28 years for intervention and control groups, respectively (15). The majority of participants were married, mirroring findings from previous studies that reported high marriage rates among patients with coronary artery disease (16,17).…”
Section: Discussionsupporting
confidence: 86%
“…Comparative analysis with existing literature indicates that while discharge education consistently improves self-efficacy, outcomes can vary based on the study design, population, and educational content delivered (19,22). This study's findings reinforce the notion that structured discharge education significantly enhances self-efficacy, corroborating earlier research emphasizing the role of comprehensive educational strategies in patient care post-discharge (15,20). The study's strengths include its rigorous methodological approach and the clear demonstration of the educational program's effectiveness.…”
Section: Discussionsupporting
confidence: 77%
“…Patients who received health education at follow-up had a significant interaction effect on improving personal control and treatment [21], [22]. It can be related to the efficacy of patient health education in increasing the patient's perception of his illness [23], [24].…”
Section: Discussionmentioning
confidence: 99%
“…Early days after ACS and the following hospitalization, patients experience a range of physical and psychological consequences such as sleep disturbance (Prado et al., 2019). It is believed that sleep disturbance can have harmful effects on ACS patients including physical stress, restlessness, aggression, reduced physical and cognitive function, mood instability and emotional distress (Bagheri et al., 2022; Farokhnezhad Afshar et al., 2017). All these increase the heart rate, respiratory rate, blood pressure, myocardial oxygen demand and cardiac dysrhythmia and can eventually lead to spreading ischemia and a second heart attack (Najafi Ghezeljeh, 2018).…”
Section: Introductionmentioning
confidence: 99%